A Penile Implant: Embodying Medical Technology - Nash, Jeffrey E. (Qualitative Sociology Review, 2021)
This article situates the experiences of having penile implant surgery between medical interventions and privately understood meanings and practices. Using my own experiences, supplemented with information from online sources, I document the changes that occur in the meanings and the practices that implant surgery enables. My analysis derives from the concepts of habitus and the looking glass body, and it begins with a diagnosis of impotence and moves through the various considerations that lead to surgery and its aftermaths. I suggest that understanding how medical technology interacts with everyday meanings contributes to a wider application of the concept of habitus while expanding a symbolic interactionist perspective of the body.